Regenera??o in vitro de Vellozia sincorana Ayensu & Smith - Borges, B?rbara Paula dos Santos (2015)
Vellozia sincorana Ayensu & SMITHis endemic of Rupestres Fields of Chapada Diamantina, popularly known as Candomb?. This species has a highly flammable resin, and the stem used to ignite wood stoves and roots to produce incense. Candomb? presents few studies in the literature, there are no studies of propagation of the species. This study aimed to develop in vitro multiplication protocol of V. sincorana, analyzing the behavior of in vitro shoots subjected to stress, and its influence on multiplication. They were used as explants in vitro shoots obtained, inoculated with concentrations of BAP (0.0; 2.22; 4.44 ?M), CIN (0.0; 2.32; 4.64 ?M) and IBA (0.0; 1.48 ?M) in MS ? medium supplemented with 87.64 mM sucrose, 1g.L-1activated carbon, and 0.7% agar (basic medium). Subsequently, it tested concentrations of cytokinins BAP or KIN (0.0; 5.0; 10.0; 15.0; 20.0 ?M). In experiments with thermal stress, flame shoots were exposed for different periods (0.0; 2.0; 4.0; 6.0; 8.0; 10 seconds), and the next tested whether the periods (0.0; 4.5; 6.0; 7.5; 9.0 min) exposure of the shoots 105 ? 1 ? C in sterilize. For drought stress basic medium was agar supplemented with different concentrations (7.0; 14.0; 21.0; 28.0 g) and the following experiment different sucrose concentrations (87.64; 175.28; 262. 92; 350.56 mM). The KIN showed greater efficacy in the multiplication in relation to BAP. The highest average for number of shoots and responsive% explants were in the periods 6, 8 or 10 seconds, being observed tolerance to water and thermal stress.